Cystatin C: factors affecting diagnostic and prognostic value in acute kidney injury - M. O. Magomedaliev; D. I. Korabelnikov (Фармакоэкономика)
The level of serum and urinary cystatin C (CysC) can be modulated by some factors (weight, gender, age, ethnicity, smoking), diseases (sepsis, cardiovascular disease, diabetes mellitus, metabolic syndrome, obesity, hypo- and hyperthyroidism) as well as administration of glucocorticosteroids, but all of them do not affect its prognostic and diagnostic value in acute kidney injury (AKI). The CysC concentration can predict adverse outcomes, such as in-hospital and out-hospital mortality, chronicity of renal dysfunction, the demand and duration of renal replacement therapy (RRT). The sCysC is an independent predictor of RRT completion in critically ill AKI patients.